Laudes Rubrics - Measurement and Learning Approach - and Laudes Foundation (Laudes Foundation, 2023)
How can we measure and learn when promoting systems change? It’s a challenge that has inspired Laudes Foundation to develop a rubrics-based methodology to help us, our partners and the wider field of philanthropy, understand our contribution to change, while learning and adapting to new and unforeseen circumstances. Change cannot be captured by numbers alone because metrics put the focus on what can be counted, not always what’s most important. Rubrics are a framework that set a standard for what ‘good’ looks like – and create a shared language for describing and assessing it using both quantitative and qualitative evidence. At Laudes Foundation, the rubrics are integrated into our grantmaking processes – from the design phase through to measurement, evaluation and learning. The four Laudes Foundation rubrics categories Laudes Foundation has developed 21 rubrics that work across different levels, from processes to long-term impact. When measuring a specific initiative, a smaller set of relevant rubrics are chosen and assessed on a rating scale from ‘harmful’ to ‘thrivable’. The 21 rubrics are categorised into four groups, with some natural overlap between categories B, C and D. Category A focuses on the process-related aspects of initiatives, including design, implementation, monitoring, communication and learning, and organisation and network effectiveness. Category B focuses on the early and later changes that need to happen to create the right conditions to achieve the 2025 outcomes. Category C captures the 2025 outcomes, focusing on how policymakers, financiers, business leaders, and workers and producers behave. Category D captures the 2030 impacts, describing the new reality created as a result of sustained efforts.